1973
DOI: 10.1172/jci107337
|View full text |Cite
|
Sign up to set email alerts
|

C2 Deficiency DEVELOPMENT OF LUPUS ERYTHEMATOSUS

Abstract: A B S T R A C T The study of serum from a patient with C2 deficiency is described. The patient had an episode of pneumococcal meningitis at 5 mo of age with seizures and transient hemiparesis and apparent purpuric skin lesions. He was first admitted to the University of Minnesota Hospitals at 10 yr of age following the discovery of proteinuria accidentally by his mother. Since then he has been admitted repeatedly to this hospital with numerous clinical findings including arthralgia, recurrent abdominal pain, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1975
1975
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…Low factor B has been noted previously to be associated with C2 deficiency (19), and it is shown that the genes for factor B and C2 are closely linked on the sixth chromosome (20). Our findings regarding factor B are of particular interest in that they suggest two populations of CZdeficient patients4ne with low normal CH50 levels and normal factor B levels, the other with low CH50 levels and low factor B levels.…”
Section: Discussionsupporting
confidence: 72%
“…Low factor B has been noted previously to be associated with C2 deficiency (19), and it is shown that the genes for factor B and C2 are closely linked on the sixth chromosome (20). Our findings regarding factor B are of particular interest in that they suggest two populations of CZdeficient patients4ne with low normal CH50 levels and normal factor B levels, the other with low CH50 levels and low factor B levels.…”
Section: Discussionsupporting
confidence: 72%
“…Four of 8 patients with pauciarticular onset had serum C2 activity selectively depressed to levels observed in individuals heterozygous for C2 deficiency (23). Recent studies have suggested that systemic lupus erythematosus-like disease may develop in patients with homozygous C2 deficiency (47,48), but disease states in relation to heterozygosity have not been thus far noted.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these individuals (>60%) do not suffer from any apparent disease, probably due to the compensatory involvement of factor B in the activation of the complement via C2 bypass mechanism (Laich and Sim, 2001). Almost 40% of individuals with C2 deficiency develop systemic autoimmune disease (Agnello et al, 1972;Day et al, 1973;Sjoholm et al, 2006). For instance, systemic lupus erythematosis (SLE) is a disease that presents with facial erythema and oral or nasopharyngeal ulceration.…”
Section: Early Components Of the Classical And Alternative Pathwaysmentioning
confidence: 99%